Nanopartículas de ouro reduzidas com Virola oleifera inibem o crescimento de Staphylococcus aureus e Pseudomonas aeruginosa - Marques, Rafaella de Resende (2020)
The presente work analyzed activity antibacterial of gold nanoparticles reduced with Virola oleífera (AuNPs-Vo). Cells of Staphylococcus aureus and Pseudomonas aeruginosa (clinic and ATCC) are used for experiments. After synthesis, AuNPs-Vo were characterizeds in localized surface plasmon ressonance (LSPR), stability (ZETA), height and disperse (DLS e TEM). In them, stability, floculation, ressuspention, antioxidant activities are avaliable. AuNPs-Vo were ressuspended in differents mediuns (DMSO 5% e 10%, PBS, e MH+) and solutions variable pH (1, 3, 5, 7, 9, 11 e 13) and concentration of NaCl (1, 2,5, 5, 10, 25, 50, 100 e 200 mmol.mL-1). Effects of differents concentrations (900 450 225 112.5 62.5 µg/mL) of AuNPs-Vo in cells developeneds (HaCaT e L929) and bacterials S. aureus e P. aeruginosa were avaliable. Recents sinthesys of AuNPs-Vo showed height monodisperse 22 nm, stables in differents mediuns (21,59 mv) and showed optimal condition for insulation at 14000 rpm and 20 min. AuNPs-Vo also showed high antioxidant activity and low toxicity. Finally, they were effective in controlling the growth of both S. aureus and P. aeruginosas, with values.